2021
DOI: 10.1002/app.50712
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hetero‐armed star‐shaped PCL‐PLA polymers with POSS core on thermal, mechanical, and morphological properties of PLA

Abstract: In this study, AB type-heteroarm star-shaped poly(ε-caprolactone)-poly(lactic acid) (PCL-PLA) polymers with polyhedral oligomeric silsesquioxane (POSS) core ((PCL) 4 -POSS-(PLA) 4 , coded as SPLA) were synthesized successfully by using ring opening polymerization and click chemistry techniques together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…However, with the addition of LCHBPs, the number of large particles increased, the average particle size of CA increased, and the distribution range of particle size became wider. The addition of 3 phr LCHBPs increased the average particle size of CA to F I G U R E 3 Micro morphologies of the PLA/CA blends fracture surface 6.01 μm and large-sized particles were appeared, which indicated that excessive LCHBPs inhibited the dispersion of CA in PLA. This may be due to the excessive selfentanglement caused by a large number of LCHBPs, which reduced the effective part of its compatibilization effect on the PLA/CA blends.…”
Section: Morphology Characterizationmentioning
confidence: 98%
See 2 more Smart Citations
“…However, with the addition of LCHBPs, the number of large particles increased, the average particle size of CA increased, and the distribution range of particle size became wider. The addition of 3 phr LCHBPs increased the average particle size of CA to F I G U R E 3 Micro morphologies of the PLA/CA blends fracture surface 6.01 μm and large-sized particles were appeared, which indicated that excessive LCHBPs inhibited the dispersion of CA in PLA. This may be due to the excessive selfentanglement caused by a large number of LCHBPs, which reduced the effective part of its compatibilization effect on the PLA/CA blends.…”
Section: Morphology Characterizationmentioning
confidence: 98%
“…Because of its extensive sources, rigidity and biodegradable nature, PLA has attracted expanded interest and therefore can be used to replace traditional plastics such as polyethylene, polypropylene, and polyethylene terephthalate 5 . However, the inherent brittleness, lack of flexibility and low crystallizability of PLA has restricted its application 6,7 . As a result, the toughening modification of PLA is necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a special family of organic–inorganic hybrid material, , polyhedral oligomeric silsesquioxane (POSS) (RSiO 1.5 ) n has a cage-shaped core, a rigid, three-dimensional structure, and a switchable branch (such as alkyl, aryl, vinyl, acrylate, epoxide, and so on) at each of the Si sites. A benefit to the organic–inorganic structure, POSS shows a huge potential for polymer performance modification according to the high solubility in most organic solutions. The POSS-grafting polymers can be prepared by free radical polymerization, ,, and the method has been used to acquire POSS–PMMA using R-POSS with CC bond branches during thermal polymerization with methyl methacrylate (MMA). The POSS-containing material with star-shaped or network structure in the polymer matrix can dramatically optimize the properties (Scheme ). ,, Considering our previous report, which shows that photosensitizer PQ can react with the CC bond of MMA more effectively, the Ma-POSS with eight methacryl (Ma) branches was selected to enhance the holographic performance of the PQ/PMMA photopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxane (POSS), a typical reactive nanoparticle with a cage core of an inorganic Si n O 1.5n nanostructure and an organic group, 15 methyl, 16 ethyl, 17 phenyl, acrylates, anhydride, and epoxides, etc as an organic group around it, 18–20 has been attracting much attention for recent years 21–25 . The inorganic cage‐like core structure of POSS provides similar good heat resistance and excellent thermoxidative stability 26,27 . For different materials and composites systems, POSS can be designed and synthesized different functional organic groups to make it have different properties 17,28–32 .…”
Section: Introductionmentioning
confidence: 99%